Extracellular vesicles from pristane-treated CD38-deficient mice express an anti-inflammatory neutrophil protein signature, which reflects the mild lupus severity elicited in these mice - Carrillo-Rodríguez, Paula; Robles-Guirado, José-Ángel; Cruz-Palomares, Adrián; Palacios-Pedrero, Miguel Ángel; González-Paredes, Elena; Más-Ciurana, Alex; Franco-Herrera, Carolina; Ruiz-de-Castroviejo-Teba, Paloma A.; Lario, Antonio; Longobardo, Victoria; Montosa-Hidalgo, Laura; Pérez-Sánchez-Cañete, María M.; et al. (Frontiers in Immunology, 2022)
In CD38-deficient (Cd38-/-) mice intraperitoneal injection of pristane induces a lupus-like disease, which is milder than that induced in WT mice, showing significant differences in the inflammatory and autoimmune processes triggered by pristane. Extracellular vesicles (EVs) are present in all body fluids. Shed by cells, their molecular make-up reflects that of their cell of origin and/or tissue pathological situation. The aim of this study was to analyze the protein composition, protein abundance, and functional clustering of EVs released by peritoneal exudate cells (PECs) in the pristane experimental lupus model, to identify predictive or diagnostic biomarkers that might discriminate the autoimmune process in lupus from inflammatory reactions and/or normal physiological processes. In this study, thanks to an extensive proteomic analysis and powerful bioinformatics software, distinct EV subtypes were identified in the peritoneal exudates of pristane-treated mice: 1) small EVs enriched in the tetraspanin CD69 and CD9, which are likely of exosomal origin; 2) small EVs enriched in CD47 and CD9, which are also enriched in plasma-membrane, membrane-associated proteins, with an ectosomal origin; 3) small EVs enriched in keratins, ECM proteins, complement/coagulation proteins, fibrin clot formation proteins, and endopetidase inhibitor proteins. This enrichment may have an inflammation-mediated mesothelial-to-mesenchymal transition origin, representing a protein corona on the surface of peritoneal exudate EVs; 4) HDL-enriched lipoprotein particles. Quantitative proteomic analysis allowed us to identify an anti-inflammatory neutrophil protein signature, which was more prominent in EVs from pristane-treated Cd38-/- mice, and quantitative differences in the protein cargo of the ECM-enriched EVs from Cd38-/- vs WT mice. These differences are likely to be related with the distinct inflammatory outcome shown by Cd38-/- vs WT mice in response to pristane treatment. Our results demonstrate the power of a hypothesis-free and data-driven approach to transform the heterogeneity of the peritoneal exudate EVs from pristane-treated mice in valuable information about the relative proportion of different EVs in a given sample and to identify potential protein markers specific for the different small EV subtypes, in particular those proteins defining EVs involved in the resolution phase of chronic inflammation.